(untitled) (The Pretoria Student Law Review, 2023)
Modernity significantly influences global action regarding social,political, and economic justice and liberation. Because of this, itsflawed origins cannot simply be ignored. This article explains thedevelopment and current conception of economic, social and politicalmodernity and shows how non-Western thought is excluded from thesespheres. The article focuses on problematising he recent construction ofmodernity by showing how modernity is founded on Western ideals.Additionally, this article tracks the spread and universalisation ofmodernity by cruel and illegitimate means like colonialism and theothering of indigenous peoples. All these form the basis for anarguments that there must be a substantial reconstruction of theconcept of modernity, and TWAIL’s relationship with international law isoffered as inspiration for such a reconstruction.